PENENTUAN KUANTITATIF ZAT WARNA KARMOSIN,PONCEAU 4R DAN MERAH ALURA YANG DITAMBAHKAN DALAM MINUMAN AGREM (Hibiscus sabdariffa, Linn) [Quantitative Determination of Carmoisine, Ponceau 4R and Allura Red Colouring Agents Added Into Softdrink Containing the - Embit Kartadarma; As’ari Nawawi; Halida . (Jurnal Teknologi dan Industri Pangan, 2007)
The synthetic food-colouring agent is stiil commonly used in soft drink to enhance the colour of the food and to make foods more attractive, particularly for the drink containing natural colour. Addition of colour is legally permitted by  the govermment, however, the product sometime contain the substance more than the permissible maximum dosage, and it  may possibly cause iillhealth to the consumer. Preparation of soft drink containing the aqueous extract of Hibiscus sabdariffa fruits gave less intense colour due to the colour. The quantity of the synthetic food colour in soft drink must be determined quantitatively for food safety and the presence of natural colour in the products may affect the results. Determination of three synthetic colouring agents, carmoisine, ponceau 4R and allura red added into soft drink containing the aqueous extract of hisbicus sabdariffa was carried out. Result showed that the determination of such colouring agents can only be achivied after adjusting the pH up to 4.5 and the recovery of carmoisine, ponceau 4R and allura red were 99.8: 100.2 and 100.0%, with the accuracy of 0.1;0.3 and 0.1% and the precission of 0.1; 0.3 and 0.1% respectively.